Penggunaan Modul Act, Believe Dan Achieve Dalam Pengajaran Bahasa Tamil Di Sekolah Jenis Kebangsaan Tamil (SJKT): The use of the Act, Believe and Achieve (ABA) Module for Tamil Language education in Tamil National-Type Schools (SJKT) in Malaysia - Veerasamy, Sheela Devi; Ramasamy , Mohana Dass; Parameswaran, Saravanan (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2025)
The main purpose of this study is to examine the use of the Act, Believe and Achieve (ABA) Module in the context of Tamil Language education in Tamil National-Type Schools (SJKT) in Malaysia. This module has been developed based on Constructivism theory and the Communicative Language Teaching (CLT) approach. Furthermore, this module integrates drama and role-play methods in Tamil Language Teaching and Learning to enhance students' communication skills and confidence in learning Tamil language in the classroom. This study was developed using a mixed-method design, namely quantitative and qualitative, involving questionnaires, semi-structured interviews, and observations. The study sample consisted of 14 Tamil language teachers from Tamil National-Type Schools in Negeri Sembilan and Selangor. Quantitative data analysis was obtained using descriptive statistics, while qualitative data was analyzed through thematic coding and triangulation. The study findings show that teachers have positive perceptions towards the implementation of the ABA Module in the classroom. Moreover, the ABA Module can increase motivation, language fluency, and creativity among students. This study affirms that pedagogy approaches based on drama and role-play are highly relevant and appropriate, aligned with the statement in the Malaysia Education Blueprint (PPPM) 2013-2025, which acknowledges that the process of implementing educational transformation requires new pedagogical approaches and methods toward mastering the skills needed in the 21st century. The study results suggest that continuous training regarding the implementation of this module needs to be provided to teachers. Additionally, support policies from school administrators in providing infrastructure facilities are also needed to conduct the Teaching and Learning activities of this ABA Module. Furthermore, the drama method approach in Teaching and Learning also needs to be included as one of the Learning Outcomes in the Curriculum Standards Document (DSKP). Tujuan utama kajian ini adalah untuk meneliti penggunaan Modul Act,Believe and Achieve(ABA) dalam konteks pengajian Bahasa Tamil(SJKT) di Malaysia.Modul ini telah dibangunkan berasaskan teori Konstruktivisme dan Pendekatan Pengajaran Bahasa Komunikatif (Communicative Language Teaching (CLT) ).Lebihan lagi, Modul ini mengintergrasi kaedah drama dan main peranan dalam Pengajaran dan Pembelajaran Bahasa Tamil untuk meningkatkan kemahiran komunikasi dan keyakinan murid dalam Pembelajaran Bahasa Tamil di bilik darjah.Kajian ini dibangunkan dengan menggunakan reka bentuk kaedah campuran iaitu kuantitatif dan kualitatif yang melibatkan borang soal selidik,temubual separa berstruktur dan pemerhatian.Samplek kajian pula terdiri daripada 14 guru Bahasa Tamil dari Sekolah Jenis Kebangsaan Tamil di Negeri Sembilan dan Srlangor.Analisis data kuantitatif diperolehi dengan menggunakan statistik deskritif.Manakala, data kualitatif dianalisis melalui pengedoan tema dan trigulasi.Dapatan kajian menunjukkan bahawa guru mempunyai persepsi positif terhadap pelaksanaan Modul ABA di bilik darjah.Lebihan lagi, Modul ABA dapat meningkatkan motivasi, kefasihan berbahasa serta kreativiti di kalangan murid.Kajian ini menegaskan bahawa pendekatan pedagogi berasaskan drama dan main peranan amat releven dan sesuai sejajar dengan kenyataan dalam PPPM 2013-2025 yang tidak menafikan bahawa proses pelaksanaan transformasi pendidikan perlukan pendekatan dan kaedah pedagogi yang baharu ke arah penguasaan kemahiran yang diperlukan pada abad ke-21.Hasil kajian mencadangkan agar latihan berterusan mengenai pelaksanaan modul ini perlu diberikan kepada para guru.Selain itu, dasar sokongan pentadbir sekolah dalam menyediakan kemudahan infrastruktur juga diperlukan untuk menjalankan aktiviti Pengajaran dan Pembelajaran Modul ABA ini.Tambahan,pendekatan kaedah Drama dalam PdP juga perlu dimasukkan sebagai salah satu Hasil Pembelajarandalam Dokumen Standard Kurikulum Pelajaran (DSKP).